Thermal performance of an MHD radiative Oldroyd‐B nanofluid by utilizing generalized models for heat and mass fluxes in the presence of bioconvective gyrotactic microorganisms and variable thermal conductivity. Issue 7 (19th August 2019) - Sohail, Muhammad; Naz, Rahila; Bilal, Sardar
Abstract: The current paper analyzes the thermal and concentration attributes with the temperature‐dependent mass diffusion coefficient and thermal conductivity for the flow of an Oldroyd‐B nanoliquid over a stretchable configuration using the Buongiorno model under the application of boundary layers. The mechanisms of heat and mass transport are modeled by using the revised definitions of heat and mass fluxes. Mathematical expressions for the conservation laws are transformed into ordinary differential expressions by making the appropriate changes. The resulting complexly structured expressions are handled via an optimal homotopy procedure. The impact of influential variables on the desired solutions is plotted, tabulated, and discussed in detail. Comparative analysis of the thermal wall flux coefficient, concentration flux coefficient, density magnitude of the motile microorganisms, and reduced dimensionless stresses with already published research as a limiting case of this exploration is presented for the validity of the proposed scheme, and an excellent agreement is observed, which confirms the reliability of the homotopic solution.